Analisis Faktor Determinan Kejadian Kek Pada Ibu Hamil Di RSIA Citra Keluarga Kediri Tahun 2015 - Ribut Eko Wijanti; Indah Rahmaningtyas; Suwoyo Suwoyo (Akademi Keperawatan Dharma Husada Kediri, 2016)
Undernutrition is still a major health problem in Indonesia, An example of undernutrition is chronic deficiency at pregnant woman. This incident brings an impact to the health of next generation, The research objective was determining factors with affect chronic energy deficiency at pregnant women in RSIA Citra Keluarga of Kediri. Design used in study is analytic method. The sampling technique used is accidental sampling. The population in this study were all pregnant womwn who reside in Antenatal Care to RSIA Citra Keluarga Kediri. The sample size used was 33 respondents. The analysis results of Spearrman test were with alpha value = 5% were 1) Education p-value = 0,009. 2) Age p-value = 0,027, 3) Parity p-value = 0,999. 4) Range pregnant p-value = 0,999. Based on this study multivariate regresi model, the factors that affect chronic energy deficiency at pregnant women are OR value of the education variable is 12,000 and OR value of the age variable is 5,595. Conclution from the study sugegested which means 12 times the maternal education affect chronic energy deficiency, and means 5,595 times the maternal age affect chronic energy deficiency. So we must do the prevention by conseling and chech body mass index before pregnant. Keywords : Incident of Cronic Deficiency in Pregnant Woman, The Dominant Affecting